Apathy exacerbates postural control impairments in stroke survivors: the potential effects of cognitive dual-task for improving postural control - Dehmiyani, Arian; Mehdizadeh, Hajar; Azad, Akram; Cheraghifard, Moslem; Jamali, Shamsi; Davoudi, Mehrdad; Shokouhyan, Seyed Mohammadreza; Taghizadeh, Ghorban (Neuropsychologia, 2022)
Apathy is a stressor and debilitating common condition for both stroke survivors and their caregivers. However, its effects on the postural control of these patients have not yet been investigated. Improved postural stability through withdrawing attention from postural control by concurrent cognitive task (i.e. dual-task condition) has been reported previously, but the effect of apathy, as a confounding factor, remains unknown. This study aimed to examine the effects of apathy and dual-task condition on postural control of chronic stroke survivors from biomechanical and neurophysiological perspectives. Twenty non-apathetic stroke survivors, 20 apathetic stroke survivors, and 20 sex-, age-, weight-, and height-matched healthy subjects were assessed using different postural sway measures and electromyography activity of ankle and hip muscles while quietly standing on rigid and foam surfaces under single-task, easy dual-task, and difficult dual-task conditions. The results showed postural instability and neuromuscular stiffening of stroke survivors, particularly apathetic stroke survivors, compared with healthy controls as evidenced by significantly greater postural sway measures and increased co-contraction of ankle muscles as well as hip muscles. Notably, concurrently performing a cognitive task significantly reduced postural instability and neuromuscular stiffening in chronic stroke survivors even in those with apathy. In conclusion, apathy exacerbates postural control impairments in chronic stroke survivors promoting an inefficient conscious mode of postural control. It is recommended that distracting the attention away from postural control by performing a concurrent cognitive task can be considered an effective strategy while designing interventions for improving postural control in apathetic stroke survivors.